Knowledge, Attitudes, and Practices About COVID-19 Among Healthcare Workers in Iran During the First Wave of the Pandemic - Hatami, Hossein; Kolahi, Ali-Asghar; Ghamari, Seyyed-Hadi; Abbasi-Kangevari, Mohsen (Frontiers in Public Health, 2022)
Background and Objective Investigating the knowledge, attitudes, and practices about the coronavirus disease 2019 (COVID-19) among healthcare workers (HCWs) could be an early step toward identifying their potential educational needs and possible factors involved in misinformation. The objective of this study was to investigate the knowledge, attitudes, and practices about COVID-19 among healthcare workers in Iran during the first wave of the pandemic. Materials and Methods The current descriptive-correlational study was conducted during the 1st days of the COVID-19 epidemic in Iran from March 24th to April 3rd, 2020. Participants included all healthcare workers at hospitals, including physicians, dentists, pharmacists, nurses, midwives, laboratory and radiology assistants, and other hospital professionals during the study period. Data were collected through an online self-administrative questionnaire. Results The responses of 1,310 participants were analyzed, of which 900 (68.7%) were female. The mean (SD) knowledge score was 25.4 (3.3), 84.7% out of 30. More than 90% of participants correctly recognized the main symptoms, transmission route, and preventive measures for COVID-19. The mean (SD) attitude score was 16.9 (1.1), 93.9% out of 18. Most participants agreed with keeping safe physical distancing, self-isolation upon symptom onset, and city lockdowns. The mean (SD) score for general practices about COVID-19 was 20.8 (2.0), 86.7% of 24. Conclusion The knowledge and practice of HCWs were appropriate, and their attitudes were mainly positive. However, there is still room for improvement regarding concerning misinformation and quackeries about COVID-19.